DEVELOPMENT AND PROSPECTS OF TOURISM INDUSTRY IN THE DIGITAL ECONOMY - Soxadaliyev Abdurashid Mamadaliyevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article focuses on the foundation of the digital economy and its key features in the tourism industry. Also, the application of digital technologies in the tourism and recreation industry, the creation of a digital online platform model "Tourism 4.0" with the widespread use of the achievements of the fourth industrial revolution.